The Relationship of Terrestrial Fern Species (Pteridophyta) at Salodik Waterfall Central Sulawesi Based on Morphological Characteristics - Dani, Dhea Pratiwi; Suleman, Samsurizal M.; Febriawan, Aan (Jurnal Biologi Tropis, 2024)
Pteridophyta ferns are a group of vascular plants that have a very long evolutionary history. This study aims to describe the relationship of terrestrial fern plant species (Pteridophyta) at Salodik Waterfall Central Sulawesi based on morphological characteristics. The method used was exploration method with the sampling technique being free collection. The data were processed using Microsoft Excel 2013 and then subjected to cluster analysis using the UPGMA (Unweighted Pair-Group Method with Arithmetic Average) method in the PAST 4.03 software (Paleontological Statistics). The research results obtained a total of 13 terrestrial fern plant species, namely Asplenium nidus, Diplazium esculentum, Davallia denticulata, Lindsaea scandens var. terrestris, Nephrolepis biserrata, Angiopteris evecta, Phymatosorus longissima, Pteris biaurita, Pteris fauriei, Selaginella doederleinii, Chingia clavipilosa, Macrothelypteris torresiana and Sphaerostephanos heterocarpus. The dendrogram of kinship between 13 species of terrestrial ferns is formed in 2 main clusters with 4 relationships categories, namely very near, near, not near, and not very near. The first category of relationship is very near with the highest Similarity Index (IS) value, namely between Macrothelypteris torresiana with Davalia denticulata (IS=86.5) and Lindsaea scandens with Pteris faurei (IS=75.2). The second category of near relationship is between Pteris biaurita with node 3 (IS=68.2), Selaginella doederleinii with node 4 (IS=64), and Diplazium esculentum with Chingia clavipilosa (IS=55.6). The third category of not near relationship is between Nephrolepis biserrata with Phymatosorus longissima (IS=27.3). The fourth category of not very near relationship with the lowest Similarity Index (IS) value is between Angiopteris evecta with Sphaerostephanos heterocarpus (IS=22.8) and Asplenium nidus with sub division Ia (IS=21.2).